Digital Surveillance, State Power, and Civil Liberties in Contemporary Indonesia - Muhammad Abdurrahman (The Indonesian Journal of Critical Legal Studies, 2026)
The rapid expansion of digital technologies has transformed governance, public administration, and security practices across the world, including Indonesia. While digital surveillance technologies offer opportunities to enhance public security and administrative efficiency, they also raise significant concerns regarding privacy, accountability, and civil liberties. This study critically examines the relationship between digital surveillance, state power, and civil liberties in contemporary Indonesia through the lens of Critical Legal Studies. Using a normative-critical approach, the research analyzes legal frameworks governing electronic information, data collection, cybersecurity, and state surveillance practices. The findings reveal that digital surveillance mechanisms increasingly expand the capacity of state institutions to monitor individuals and regulate public behavior. However, legal safeguards concerning privacy rights, transparency, and oversight mechanisms remain insufficient in addressing potential abuses of power. The study demonstrates that surveillance technologies are not merely technical instruments but are embedded within broader political and legal structures that shape relationships between citizens and the state. From a critical perspective, the expansion of surveillance capabilities may reinforce asymmetrical power relations and limit democratic freedoms when accountability mechanisms are weak. The research argues that effective regulation must balance legitimate security objectives with the protection of constitutional rights and civil liberties. Strengthening judicial oversight, data protection standards, and public accountability frameworks is essential for maintaining democratic governance in the digital era. The study concludes that critical examination of surveillance law is necessary to prevent the normalization of excessive state control and to safeguard individual freedoms within Indonesia’s evolving digital society.